The origins of neoliberalism : insights from economics and philosophy - Becchio, Giandomenica; Leghissa, Giovanni, 1964- (New York : Routledge, 2017)
Neoliberalism is a doctrine that adopts a free market policy in a deregulated political framework. In recent years, neoliberalism has become increasingly prominent as a doctrine in Western society, and has been heavily discussed in both academia and the media. In The Origins of Neoliberalism, the joint effort of an economist and a philosopher offers a theoretical overview of both neoliberalism's genesis within economic theory and social studies as well as its development outside academia. Tracing the sources of neoliberalism within the history of economic thought, the book explores the differences between neoliberalism and classical liberalism. This book's aim is to make clear that neoliberalism is not a natural development of the old classical liberalism, but rather that it represents a dramatic alteration of its original nature and meaning. Also, itfights againstthe current idea according to which neoliberalism would coincide with the triumph of free market economy. In its use of both history of economics and philosophy, this book takes a highly original approach to the concept of neoliberalism. The analysis presented here will be of great interest to scholars and students of history of economics, political economy, and philosophy of social science.
Introduction: the counter-revolution of neoliberalism -- Foucault and beyond -- The building of economics as a science -- The building of individuals as rational agents -- Turning the world into a firm -- Postscript: a new ethics for a new liberalism? -- Index.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Neoliberalism; Economics -- History; Social sciences -- Philosophy; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General